Zastopanost družboslovnih vsebin na primarni stopnji izobraževanja v nekaterih evropskih državah - Plazar, Sonja; Hus, Vlasta (Revija za elementarno izobraževanje, 2008)
Social Contents for Primary Level Education in Selected European Countries. This article presents a comparison of selected countries that are trying to add social subjects to the primary level curriculum. We have taken into consideration the following European countries: Slovenia, Great Britain, Germany, Italy andFinland. We did a comparison and analysis of chosen criteria for the proposed social subjects of each country. We found differences in the following categories: the proposed design of the classes, the estimated extent of social content, the number of teaching hours and the number of classroom hours.